2017
DOI: 10.1080/10894160.2018.1384263
|View full text |Cite
|
Sign up to set email alerts
|

Theorizing the lesbian hashtag: Identity, community, and the technological imperative to name the sexual self

Abstract: This analysis integrates poststructuralist and symbolic interactionist approaches to the self by incorporating the insights of science and technology studies regarding categorization processes. While the advent of the Internet has freed many individuals from geographical constraints on community formation, the architectures of online platforms produce a technological imperative to name aspects of the self with words. Using sexual identity hashtags on Instagram (e.g., #lesbian) thus performs paradoxical functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 24 publications
0
22
0
1
Order By: Relevance
“…This suggests an expansion of the notion of lesbian identity to include a wider array of signals of non-heterosexual female identity. Aligning with Herrera’s (2017) finding that WSW on Instagram default to #lesbian for its recognizability, participants often defaulted to stereotypically lesbian self-presentations in order to be rapidly identifiable as non-heterosexual. However, many participants did not personally identify as “lesbian” and used identity-related terms like “gay” and “queer” interchangeably.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…This suggests an expansion of the notion of lesbian identity to include a wider array of signals of non-heterosexual female identity. Aligning with Herrera’s (2017) finding that WSW on Instagram default to #lesbian for its recognizability, participants often defaulted to stereotypically lesbian self-presentations in order to be rapidly identifiable as non-heterosexual. However, many participants did not personally identify as “lesbian” and used identity-related terms like “gay” and “queer” interchangeably.…”
Section: Resultsmentioning
confidence: 82%
“…Jamie (24, UK) explained, “I am very literal in that, I just assume, if you’re on Gay Tinder, then you’re gay, well not gay, but queer.” For participants, Gay Tinder described a portion of the app dominated by LGBTQ+ people, assumed to be the only ones to change their gender settings due to the heteronormative uptake and discourses surrounding Tinder. Jamie invoked “gay,” and used it interchangeably with “queer,” to construct a broad category of non-heterosexuality, reflecting young people’s ambivalence toward specific identity terms (Herrera, 2017) and the popular uptake of “gay” as a catch-all for the wide spectrum of sexual identity beyond “straight” or heterosexual. 3 Our participants imagined themselves entering a space—whether or not they specifically called it Gay Tinder—where only WSW should be visible.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although platforms pose challenges, such as privacy risks (Cho, 2017), the circulation of LGBTQ self-representations on social media can contribute to individuals’ sexual identity development, community-building, and challenges to heteronormative discourses (Cooper & Dzara, 2010). For example, Herrera (2017) found that queer women’s self-representations on Instagram that were paired with lesbian-related hashtags enabled individuals to claim an “intelligible sexual identity” (p. 11) while feeling like part of a community. However, the commercialization of, and marketing toward, minority sexual identities can dilute counterpublic discourse and meaningful community formation (Campbell, 2005; Lovelock, 2017).…”
Section: Tensions Of Labor and Self-representationmentioning
confidence: 99%